Adab Guru Menurut Pemikiran Imam Al-Nawawi dalam Kitab Adab Al-‘Alim Wa Al-Muta'allim - Supraha, Wido; Juhaepa, Juhaepa (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2021)
This paper aims to know the adab of teachers when doing teaching activities according to the thinking of Imam al-Nawawi in his work Adab Al-'Alim Wa Al-Muta'alim, which is also obtained other adab-adab for a teacher in this study consisting of adab as a teacher against himself, and adab teacher to his lessons and busyness. This research method uses descriptive methods whose analysis is done qualitatively. The technique of data collection is done through library research by reading, recording and processing research materials. The results of this study summarized four important points about a teacher's adab against him, then adab teacher to the lesson and his busyness consists of important issues that were successfully formulated by researchers, as well as approximately 14 adab that must be applied by a teacher when doing the process of teaching knowledge to his students.Abstrak Tulisan ini bertujuan untuk mengetahui adab guru ketika melakukan aktivitas pengajaran menurut pemikiran Imam al-Nawawi dalam karyanya Adab Al-'Alim Wa Al-Muta'alim, yang mana didapatkan pula adab-adab yang lain bagi seorang guru dalam kajian ini yang terdiri dari adab seornag guru terhadapa dirinya, dan adab guru terhadap pelajaran dan kesibukannya. Metode penelitian ini menggunakan metode deskriptif yang analisisnya dilakukan secara kualitatif. Tekhnik pengumpulan datanya dilakukan melalui studi kepustakaan (library research) dengan cara membaca, mencatat serta mengolah bahan penelitian. Hasil dari penelitian ini dirangkum empat poin penting mengenai adab seorang guru terhadap dirinya, kemudian adab guru terhadap pelajaran dan kesibukannya terdiri dari tuju poin penting yang berhasil dirumuskan oleh peneliti, serta kurang lebih 14 adab yang mesti diterapkan oleh seornag guru ketika melakukan proses mengajarkan ilmu kepada peserta didiknya.